Parenting: Menanaman Kebiasaan Merawat Gigi Sejak Dini - Dewi, Triana Puspa; Dzihny, Kholy; Agustiana , Santi; Sulastri, Fitri (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
Dental health problems in early childhood are often ignored by parents, which can lead to more serious dental health problems in the future. This Community Service Program (PKM) aims to increase the knowledge of parents and children about the importance of early dental care. The proposed solution is through parenting socialization that includes educational materials and practical techniques in caring for teeth. The method of implementing the activity includes delivering material through lectures and discussions, demonstrating dental care techniques, and utilizing fables as an interesting educational media for children. The findings of this activity showed that there was a significant increase in parents' and children's understanding of the importance of dental care, as well as positive changes in dental care habits at home. The final evaluation showed that this activity was effective in increasing dental care awareness and skills, with recommendations for regular implementation of similar programs and the addition of more innovative learning methods.